Effects of traffic density on performance of reactive routing protocols - Kanchan K.; Gupta S.C. (My University, 2025)
A Mobile ADhoc NETwork, MANET is a collection of autonomous wireless mobile nodes forming frequently changing network topology. Nodes communicate with each other through wireless links that needs efficient dynamic routing protocols. Transmission range of wireless network interfaces is limited, so if any node wants to exchange data with another node across the network it needs multiple hops. As there is no stationary infrastructure such as base stations, mobile nodes need to operate as routers to maintain the information about the network connectivity. A number of routing protocols have been proposed for ad hoc wireless networks. In this paper, we study and compare the performance of the two prominent reactive MANET routing protocols: Dynamic Source Routing (DSR) and Ad Hoc On-Demand Distance Vector Routing (AODV). The performance analyzed through NS2 based simulation by varying source destination pairs and pause time. © 2013 IEEE.